The dsRNA-dependent kinase (PKR) inhibits the growth of Leishmania major via NF-κB-mediated genes - Áislan de Carvalho Vivarini; Bianca Cristina Duarte Vivarini; Yuri Nunes Oliveira; Flavia Thiebaut; Evelize Folly das Chagas (Parasitology)
Parasites of the Leishmania species have been observed to infect macrophages and thereby modulate the host microbicidal responses, resulting in a wide spectrum of diseases. A comprehensive experimental mapping of the relationship between the double-stranded RNA protein kinase R (PKR) and NF-κB pathways in the outcome of the infection was conducted in an effort to improve the understanding of the biology associated with the parasites–host cell interaction. The results showed that in the absence of PKR and Type I Interferon (IFN) signalling, L. major infection was enhanced. The levels of PKR and gene promoter activation were evaluated. The results showed that infection did not induce PKR expression by inhibiting the phosphorylation of STAT1 and subsequent binding in the PKR promoter. However, infection induced PKR phosphorylation but did not prevent subsequent signalling through this pathway. To address the role of activation of these signalling, the induction of PKR-dependent gene expression was examined. Activation of the classical p65/p50 dimer was found to be dependent on the PKR in the L. major infection, which was essential for the induction of iNOS, IFNβ and tumour necrosis factor expression. In addition, macrophages treated with nuclear factor-kB inhibitors were more susceptible to infection. Furthermore, translocation of the p65/p50 to the promoters of these genes increased in a PKR-dependent manner. Collectively, these results suggest that macrophages retain their ability to induce important downstream effectors in PKR signalling. These effectors contribute to protection in pathogenesis, reducing parasite proliferation and regulating the inflammatory genes that, consequently, modulate the activation state of macrophages during infection.